PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA DAN MOTIVASI SERTA DAMPAKNYA PADA KINERJA PEGAWAI PDAM WONOGIRI - Pebrianto, Dede; Hamdani, Anwar (Arthavidya Jurnal Ilmiah Ekonomi, 2017)
ABSTRACTThis study aims is to determine the influence of organizational culture and compensation to job satisfaction and motivation and its impact on employee performance at PDAM Wonogiri. The data is primary data by sampling samples in this study were 100 employees at PDAM Wonogiri. Sampling technique in this study using census data in this research will be obtained directly from the results of the questionnaire. The analytical tool used Test Instrument Research, Testing linearity, analysis and regression lines by t test, F test and test R2.T test results showed that organizational culture has significant influence on job satisfaction. Compensation has significant influence on the job satisfaction. Organizational culture has significant effect on motivation. Compensation has significant effect on motivation. Cultural organizations has a significant effect on employee performance. Compensation has significant effect on employee performance. Employee satisfaction has significantly influence on employee performance. Employee motivation has significant effect on employee performance. Simultaneously test results (Test F) can be inferred simultaneously that organizational culture, compensation, job satisfaction and employee motivation have positive and significant impact on employee performance. R2 total of 99.7%. This means that the employee's performance is explained by organizational culture, compensation, job satisfaction and motivation of employees by 99.7% and the remaining 0.3% is explained by other variables outside model such . the competence. The conclusion of this path analysis showed that the use of an intervening variable of job satisfaction and motivation of employees in order to improve performance, to variable organizational culture is not effective. The most effective path to improving employee performance is the direct path of organizational culture on employee performance, because it has the greatest influence, positive and significant.Keywords : organizational culture, job satisfaction and motivation compensation, employee performance